Paraplegia in young female after stab injury: a rare injury with heavy socioeconomic burden and its impact - Wandile, Kiran Narayanrao; Mote, Girish Balasaheb; Badole, Chandrashekhar Martand (International Journal of Research in Medical Sciences, 2017)
Thoracic spinal cord stab injuries are rare lesions. We report a 32 years old young married female, of a lower middle class, who was stabbed on her back with a sickle by her neighbor after a quarrel. She presented with complete paraplegia with muscle power of zero on all muscle groups, complete sensory loss from thoracic dermatome level 4 and below, acute urinary retention, and a 3-centimeter vertically placed wound on the posterior thoracic region from which cerebrospinal fluid mixed with blood was oozing out. A high-dose methylprednisolone protocol was started (30 mg/kg in one hour and then 5.4 mg/kg over next 23 hours), urinary catheter placed and sterile cleaning and dressing was done. Antibiotics and analgesics were also administered. The Magnetic Resonance Imaging scan was done urgently and scanning revealed thoracic spinal cord contusion at D5 vertebral level with cord oedema at D4 to D6 vertebral level and fracture spinous process of T4 vertebral body. The case is managed conservatively and she is under follow up. As patient is a young married female, wedge worker by occupation, having lower middle class of socioeconomic status, this condition has high impact considering the socioeconomic issues.